Post-traumatic stress disorder and associated factors among people who experienced traumatic events in Dessie town, Ethiopia, 2022: A community based study - Anbesaw, Tamrat; Zenebe, Yosef; Asmamaw, Amare; Shegaw, Maregu; Birru, Nahom (Frontiers in Psychiatry, 2022)
Background Posttraumatic stress disorder (PTSD) may develop as a serious long-term consequence of traumatic experiences, even many years after trauma exposure. Dessie town residents have experienced prolonged armed conflict due to inter-communal conflict in 2021. Those people are exposed to different kinds of trauma, and violence, making them more prone to psychological disorders. Despite the highest number of people affected due to conflict and its negative impact on mental health, post-traumatic stress disorders among people are overlooked in Ethiopia. This study aimed to assess the prevalence and associated factors of post-traumatic stress disorder among people who experienced traumatic events in Dessie town, Ethiopia, 2022. Materials and methods Community based cross-sectional study was conducted on June 8–July 7, 2022, by using a multi-stage cluster sampling with a total sample of 785. Pretested, structured questionnaires and face-to-face interviews were used for data collection. PTSD was assessed by the Post-traumatic stress disorder Checklist for DSM-5 (PCL-5). Data was entered using Epi-data version 3.1 and, then exported to SPSS version 26 for analysis. The association between outcome and independent variables was analyzed with bi-variable and multivariable logistic regression. P-values less than 0.05 was considered statistically significant. Result The prevalence of PTSD among Dessie town residents was found to be 19.4% (95% CI, 16.7, 22.0). In multivariable analysis, being females (AOR = 1.63, 95% CI 1.10–2.44), previous history of mental illness (AOR = 3.14, 95% CI 1.14–7.06) depressive symptoms (AOR = 3.12, 95% CI 1.92–5.07), witnessing a serious physical injury of a family member or friend (AOR = 2.82, 95% CI 1.18–6.70) and high perceived life threats (AOR = 5.73, 95% CI 3.05–10.78) were found to be significant predictors of PTSD. Conclusion The prevalence of PTSD among Dessie town residents was found to be huge. Being female, having a previous history of mental illness, depressive symptoms, witnessing a serious physical injury of a family member or friend, and high perceived life threats were variables that are independent predictors of PSTD. People who have experienced such a severe traumatic event require psychosocial support to aid in their recovery from the terrible experiences.